LEGAL SECURITY ON CELLPHONE TRADING THROUGH ELECTRONIC MEDIA IN INDONESIA - Aswari, Aan; Pasamai, Syamsudin; Qomar, Nurul; Abbas, Ilham (Jurnal Dinamika Hukum, 2017)
The rapid growth of technology development brings impact on human life related to its utilization. This article analyzes legal security through several components in a cellphone trading through electronic media. This study is a conceptual idea and shows that the implementation of legal security in several components should provide solution to any potential conflicts. A good intention component should be applied to form an ideal legal relation from the beginning to the end and realization in performing its obligation reflect the concrete aspect. Warranty provides protection security for related parties with some governing regulations during transaction. However, some other supporting components have not been effectively contribute to balance the utilization of technology in trading.Keywords: legal security, trading, cellphone, electronic media